Quantum-Enabled Secure and Energy-Efficient Protocols for Smart Grid Communication Systems - Sara Al-Qaraghuli; Sarah Haitham Jameel; Mohammed Nouri Majid; Aqeel Mahmood Jawad; Matai Nagi Saeed; M Batumalay (Malikussaleh University, Aceh, Indonesia, 2025)
The development and evolution of the smart grid into complex, cyber-physical energy systems make it essential to secure?communication among the distributed components. The rise of quantum computing has made it even more pressing to develop protocols that?are secure outside the limitations of classical cryptosystems. In this paper, it proposes a quantum-assisting secure communication scheme (QASCP) to?boost the security and energy for smart grid communication systems. The proposed protocol combines quantum key distribution with lightweight entropy-based mutual authentication and dynamic session management. It is designed to defend grid assets such as control centers, smart meters, and distribute energy?resources from sophisticated adversarial models, including quantum-capable threats. The approach consists of system level simulation utilizing a?co-simulation framework customized for quantum smart grid communication. The performance of this scheme was compared?against classical and PQ lattice-based schemes in terms of the authentication latency, energy consumption, entropy preservation, and scalability to handle the load and delay effects, under the assumptions of different loading and delay scenarios. Simulation results show that QASCP is able to reduce the energy consumption and authenticity latency, simultaneously it keeps the high throughput and leaves strong entropy?under attack scenarios. The protocol is also shown to?remain robust with varying quantum bit error rates as well as having a smaller memory footprint on popular network topologies. The results provide evidence for the practical integration of?quantum-secure communication in smart grid architectures. By addressing security and performance simultaneously, the protocol?provides a path to future-proof energy networks which can support dependable operations in a quantum-enhanced environment. This could be future enhance for energy efficiency.